2017
DOI: 10.1002/hep.29079
|View full text |Cite
|
Sign up to set email alerts
|

Bile duct ligation–induced biliary hyperplasia, hepatic injury, and fibrosis are reduced in mast cell–deficient KitW‐sh mice

Abstract: Activated mast cells (MCs) release histamine (HA) and MCs infiltrate the liver following bile duct ligation (BDL) increasing intrahepatic bile duct mass (IBDM) and fibrosis. We evaluated the effects of BDL in MC deficient mice. Methods: WT and KitW-sh mice were subjected to sham or BDL for up to 7 days and KitW-sh mice were injected with cultured mast cells or 1X PBS before collecting serum, liver blocks and cholangiocytes. Liver damage was assessed by H&E and ALT levels. IBDM was detected by CK-19 expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
120
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 60 publications
(126 citation statements)
references
References 48 publications
(160 reference statements)
5
120
1
Order By: Relevance
“…Instead, the collagen content (as marked by hydroxyproline content) was somewhat higher in the MC‐deficient as compared with the MC‐competent rats, indicating a protective role of MCs . In contrast to these studies, the extent of liver fibrosis developing after bile duct ligation was reduced in MC‐deficient W sh /W sh mice in comparison with MC‐sufficient controls …”
Section: Mast Cells In Models Of Liver Fibrosiscontrasting
confidence: 63%
See 1 more Smart Citation
“…Instead, the collagen content (as marked by hydroxyproline content) was somewhat higher in the MC‐deficient as compared with the MC‐competent rats, indicating a protective role of MCs . In contrast to these studies, the extent of liver fibrosis developing after bile duct ligation was reduced in MC‐deficient W sh /W sh mice in comparison with MC‐sufficient controls …”
Section: Mast Cells In Models Of Liver Fibrosiscontrasting
confidence: 63%
“…202 In contrast to these studies, the extent of liver fibrosis developing after bile duct ligation was reduced in MC-deficient W sh /W sh mice in comparison with MC-sufficient controls. 206…”
Section: Mast Cells In Models Of Liver Fibrosismentioning
confidence: 99%
“…Another study has shown that serum levels of histamine are increased in Mdr2 −/− mice, and inhibition of mast cell-derived histamine secretion decreases serum histamine levels as well as bile duct hyperplasia and fibrosis in these mice [70]. Mast cell-deficient mice show less liver damage, bile duct mass, and fibrosis during BDL compared to wild-type [71]. These studies suggest that histamine secreted from mast cells infiltrated during cholestatic liver injury interacts with histamine receptors and regulates cholangiocyte responses leading to bile duct hyperplasia and fibrosis.…”
Section: Pathways Associated With Cholangiocyte Responses and Theimentioning
confidence: 99%
“…SCF receptor) on their surface [12,13]. We have demonstrated that, during PSC (both in rodent models and human liver tissues), MC infiltration increases and MCs reside close by bile ducts, allowing for an interaction with cholangiocytes [11,14]. Additionally, it has been shown that cholangiocytes secrete increased amounts of SCF during damage such as cholangiocarcinoma (CCA) and during liver regeneration [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…After migration to the liver, MCs contribute to hepatic fibrosis by promoting HSC activation and also play a role in enhancing inflammation [11,14,17]. Multiple studies from our group have demonstrated how inhibition of MC mediators (i.e.…”
Section: Introductionmentioning
confidence: 99%